Effect of TiO2 on phase composition and microwave dielectric properties of Zn1.01Nb2O6 ceramics. (August 2017) - Zhang, Jie; Yue, Zhenxing; Li, Longtu
Abstract: Nonstoichiometry has been playing an important role in the microwave dielectric performance of columbites A 2+ Nb2 O6 (A 2+ = Ca, Mg, or a transition metal). Herein, with an excess of 0.01 mol Zn, the Q × f values of ZnNb2 O6 ceramics could be effectively improved from 121, 000 GHz to 138, 000 GHz. On the basis of high- Q Zn1.01 Nb2 O6 ceramics, TiO2 was chosen to further tune the τ f values for the matrix materials prepared by the conventional solid-state reaction method. The results showed that, with the increase of TiO2 content, the ZnNb2 O6 -based ceramics underwent four phase regions: columbite (ZnNb2 O6 ) solid solution, ixiolite (ZnTiNb2 O8 ) solid solution, mixture of ZnTiNb2 O8 and rutile (Zn1/3 Nb2/3 )0.5 Ti0.5 O2, and (Zn1/3 Nb2/3 )0.5 Ti0.5 O2 solid solution. Such changes in phase formation had an important influence on the microwave dielectric behavior of (1− x )Zn1.01 Nb2 O6- x TiO2 ceramics. Importantly, τ f could be tuned from −15.3 ppm/°C to +13.9 ppm/°C along with x increased from 0.58 to 0.6. Accompanied with ε r ≈ 44.64 ~ 47.43 and Q×f  ≥ 12, 300 GHz, these materials are promising candidates for applications in microwave components and devices.